HCI in Business, Government and Organizations: 11th International Conference, HCIBGO 2024, Washington, DC, June 29 – July 4: Proceedings, Part I - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2024)
This two-volume set of HCIBGO 2024 constitutes the refereed proceedings of the 11h International Conference on HCI in Business, Government and Organizations, held as part of the 26th International Conference, HCI International 2024, which took place in from June 29 - July 4, 2024 in Washington DC, USA. Two volumes of the HCII 2024 proceedings are dedicated to this year’s edition of the HCIBGO conference. The first covers topics related to Digital Commerce and Marketing, Artificial Intelligence in Business, and Workplace, Well-being and Productivity. The second focuses on topics related to Teleworking and Virtual Collaboration, and Improving User Experience and Service Efficiency.